Dynamics and ecology of an Indo-Pacific conch, Conomurex persicus(Mollusca: Gastropoda) in southeastern Turkey - Mutlu, Erhan (2006)
Conomurex persicus, one of the tropical conchs, has been introduced to one of the subtropical regions, the northeastern Mediterranean Sea, and invaded sandy bottoms between 1 and 10 m deep. Population dynam-ics were studied from specimens collected with a standard dredge (60 x 15 cm mouth opening, 0.5 x 0.5 cm eye opening of net). Samples of C. persicus were collected monthly along the 5 and 10 m depth contours off Erdemli, Mersin, Turkey, in February and May 2000. Intra-annual density depended on salinity levels, while inter-annual density was correlated with bottom water temperature. Specimens underwent spring emergences and winter burial and sheltering (disappearance). Emergence took place in March when temperatures rose and the disappearance occurred in October-November when temperatures dropped. Adults live at 10 m, juveniles are recruited at a 5 m depth. Recruitment began in April and continued for the next 6 months. In contrast to shell width or shell lip thickness, shell length was not a convenient index for estimation of growth parameters. Annual production and mortality were calculated to be 7.86 g m-2 and 3.80 g m-2, respectively, in April-November.